2020
DOI: 10.3389/fcell.2019.00356
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects and Treatment Potential of Incretin Mimetics in a Murine Model of Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a commonly occurring injury in sports, victims of motor vehicle accidents, and falls. TBI has become a pressing public health concern with no specific therapeutic treatment. Mild TBI (mTBI), which accounts for approximately 90% of all TBI cases, may frequently lead to long-lasting cognitive, behavioral, and emotional impairments. The incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are gastrointestinal hormones that induce glucosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 102 publications
0
21
0
Order By: Relevance
“…Next, the mouse is exposed to one familiar object (A) and one novel object (B) in the same site during familiarization training after 24 h and 72 h of TBI. Again, the amount of time spent near each object was recorded and determined the cognitive status, as reported previously in TBI [38,39]. The plexiglass apparatus was cleaned with 70% ethanol between tests with each mouse.…”
Section: Weight Drop-induced Closed-head Acute Tbi Model Andmentioning
confidence: 99%
“…Next, the mouse is exposed to one familiar object (A) and one novel object (B) in the same site during familiarization training after 24 h and 72 h of TBI. Again, the amount of time spent near each object was recorded and determined the cognitive status, as reported previously in TBI [38,39]. The plexiglass apparatus was cleaned with 70% ethanol between tests with each mouse.…”
Section: Weight Drop-induced Closed-head Acute Tbi Model Andmentioning
confidence: 99%
“…52 There are 3 fluoro-jade dyes-Fluoro-Jade, Fluoro-Jade B, and Fluoro-Jade C. 53 Fluoro-Jade B, and Fluoro-Jade Care extensively used for identifying and quantifying degenerated neurons in neurotrauma studies. [54][55][56][57][58][59] In this study, we used Fluoro-Jade B to stain and quantify the degenerating neurons in the stab wound injury. Results showed large number of degenerating neurons around the injury site in injured + treated with PBS (I + PBS1 and I + PBS2 groups) and injured + IFNγ or IL-1β treated groups (I + IFN-γ and I + IL-1β) a day after injury, with a significant difference between PBS-treated and IFN-γ-or IL-1β-treated groups.…”
Section: Il-1β Are Able To Increase Secretion Of Bdnf Through Astrocymentioning
confidence: 99%
“…46 Similar enhancement of microglial/astrocytes population after traumatic injury has been shown in several studies. [54][55][56]61 Gradual decrease in the number of degenerating neurons in injured and treated with IFN-γ (I + IFN-γ) and IL-1β (I + IL-1β) groups from first day to seventh day postinjury may be due to specific trophic neuroprotective effects of IFN-γ and IL-1β directly or through enhancement of microglia and astrocytes, thereby enhancing the neurotrophic factors such as BDNF as observed in this study, which may be one of the many neurotrophic factors provided neuroprotection. We have reported similar enhancement of astrocytes, microglia and BDNF by dibutyryl cyclic adenosine monophosphate (dBcAMP), a synthetic analogue of cAMP.…”
Section: Il-1β Are Able To Increase Secretion Of Bdnf Through Astrocymentioning
confidence: 99%
“…In the present study, it is not possible to say to what extent the changes in proteins observed in the cortical arrays are explicitly due to reductions or increases in protein synthesis or if the changes are due to a loss or increase in cell numbers in the injured cortex. It is, however, worth considering that our prior work using this mild model of TBI with a 30 g weight has provided evidence of diffuse neuronal cell degeneration observed at 72 hr following mTBI, additionally we have observed losses of neurons at 7 and 30 days following mTBI ( Bader et al, 2019a , Bader et al, 2019b ; Benady et al, 2018 ; Lecca et al, 2019 ; Rubovitch et al, 2015 ). As such, we are not able to exclude the possibility that the reductions in the proteins observed in the cortical arrays are due to a loss of cells in the animal brains and not solely due to a reduction in expression of the proteins.…”
Section: Discussionmentioning
confidence: 71%